2017
DOI: 10.1002/adfm.201606385
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Robust Silica Coatings with Dual Range Porosity for Enzyme‐Based Optical Biosensing

Abstract: Hierarchically porous transparent silica coatings combine large specific surface area with enhanced pore accessibility for optical biosensing. This paper describes a versatile approach to fabricate optically transparent silica coatings with multiscale porosity. Thin films (around 1 μm in thickness) of an aqueous suspension of primary silica aggregates form a mesoporous, interconnected matrix, and sacrificial polymer particles template well‐defined, discrete macropores with high structural integrity. The total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The detection limit of the sensor was as low as 80 nM . In another study a transparent multiscale porous Si-NP thin film was developed for the immobilization of HRP and lactate dehydrogenase enzyme. , …”
Section: Surface Functionalization Of Si-nps For Biomedical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit of the sensor was as low as 80 nM . In another study a transparent multiscale porous Si-NP thin film was developed for the immobilization of HRP and lactate dehydrogenase enzyme. , …”
Section: Surface Functionalization Of Si-nps For Biomedical Applicationmentioning
confidence: 99%
“…95 In another study a transparent multiscale porous Si-NP thin film was developed for the immobilization of HRP and lactate dehydrogenase enzyme. 96,97 From the above discussion, it is worth mentioning that MSNs can be used effectively for electrochemical biosensing and they are highly suitable for future applications in early detection of diseases, pathogens, and biotargets.…”
Section: Si-nps In Biosensingmentioning
confidence: 99%
“…Magnetic microspheres with hierarchical porosity (PFMMs) were non-conventional precursor-a novel rigid-flexible dendrimer synthes Across numerous studies, hierarchical porosity of biocatalyst supports has been shown to be crucial in influencing the biocatalyst performance [57,58,[61][62][63][64][65][66]. The advantages of hierarchical porosity are threefold: (i) small pores (micropores) provide structural integrity of the support, (ii) large pores (large meso-and macropores) allow an improved mass transfer of the substrate, (iii) while the medium-sized pores (mesopores, which are larger than the enzyme size) can result in optimal self-assembly of enzyme molecules inside the pores, resembling the degree of crowding realized in cells.…”
Section: Porosity Influence On the Biocatalyst Performancementioning
confidence: 99%
“…[18] The above research shows that using fluoropolymer to reduce surface energy and controlling surface roughness could simultaneously achieve the hydrophobicity and transparency of organic coatings, which are with potential conflict recognized as one of the most challenging issues for anti-fingerprint coating's designing. [19][20][21][22][23][24] Furthermore, fabricating micro/nano-structure is typically one of the strategies for regulating surface roughness. Cao et al fabricated porous Si films by a convenient gold-assisted electroless etching process, which possess a hierarchical porous structure consisting of micrometer-sized asperities superimposed onto a network of nanometer-sized pores.…”
mentioning
confidence: 99%